Genomic Medicine in Developing Countries and Resource-Limited Environments (2017)
Even though the translation of genomic discoveries into clinic and public health has gained momentum, major discrepancies still occur between developed and developing/resource-limited countries. Genomic medicine is implemented at a different pace not only due to limited resources but also because of the slow pace toward the adoption of new findings. The potential of genomic medicine to rationalize medical diagnosis and treatment has been poorly understood. In this chapter, we discuss examples from the successful implementation of genomic medicine in developing countries. We feel that these examples can serve as model cases toward the implementation of genomic medicine in resource-limited environments. © 2017 Elsevier Ltd. All rights reserved.